The Influence of Brand Ambassadors And E-Trust on E-Loyalty of Consumers on The Tokopedia Platform (Case Study on BTS as a Brand Ambassador Tokopedia) - Cibro, Elfi Juliana; Fikri, Miftah El (Economic: Journal Economic and Business, 2025)
This study aims to determine the effect of Brand Ambassador and E-Trust on consumer E-Loyalty on the Tokopedia platform, using BTS as a case study. This research uses a quantitative approach with a deskriptif method. Data was collected through questionnaires distributed to 100 active students at Universitas Negeri Medan from the 2021 batch who have used Tokopedia. The data analysis technique used is multiple linear regression. The results show that Brand Ambassador has a positive and significant effect on E-Loyalty, as does E-Trust, although with a smaller coefficient value. Simultaneously, both variables significantly affect E-Loyalty. This study implies that using relevant and credible public figures can enhance customer loyalty on e-commerce platforms.